AI and Trust. - Schneier, Bruce (Communications of the ACM, 2025)
A speech is presented by Bruce Schneier on the topic of artificial intelligence (AI) and trust, delivered during the 2025 Rivest-Shamir-Adleman (RSA) Conference in San Francisco, California, on April 29, 2025.